Determination of Anisotropic Crystal Optical Properties Using Mueller Matrix Spectroscopic Ellipsometry. (2016) - Postava, K.; Sýkora, R.; Legut, D.; Pištora, J.
Abstract: In this paper the Mueller matrix ellipsometry in the spectral range from 0.73 to 6.4 eV measured using dual rotating compensator ellipsometer RC2 (Woollam company) is applied to study anisotropic crystals. First we summarize the effects of optical anisotropy to Mueller matrix spectra. As an example of an uniaxial sample we have characterized a Rutile (TiO2 ) tetragonal crystal. The optical axis of the sample is parallel to its surface. The sample is characterized at variable angle of incidence and variable azimuthal rotation angle. The Mueller matrix spectra are fitted to the model based on Kramers-Kronig consistent Basis spline and obtained optical functions are compared with tabulated data and ab-initio models based on first-principle calculated electronic structure.